Compliance In Broiler Agribusiness Partnership Contracts at PT. Ciomas Adisatwa Makassar Unit - Muh. Ridwan; Andi Tenri Rakiyah; St. Rohani (Ilomata International Journal of Management, 2021)
Partnership is a business strategy carried out by two or more parties within a certain period of time to gain mutual benefits with the principle of mutual need and mutual growth. Because it is a business strategy, the success of the partnership is largely determined by the compliance among partners in carrying out business ethics. In this context, the parties who are directly involved in the partnership must have the basics of business ethics that are mutually understood and embraced as a starting point in running the partnership. This study is objected to determine the compliance level of the company PT. Ciomas adisatwa Makassar Unit as the core in the broiler agribusiness partnership contract. This study was conducted from January 2020 to February 2020. The sample in the study was 31 breeders who partnered with PT. Ciomas Adisatwa Makassar Unit. Data collection was carried out using farmer data recorded in the core company and farmer interviews. The data analysis used in this research is using the Champion formula. The result of the study indicates that the compliance level of the core company PT. Ciomas Adisatwa Makassar Unit in the broiler chicken agribusiness partnership system is in the compliant category (compliance rate of 81.81%). Keywords: Agribusiness, Broiler, Partnership, Compliance.